Target cuing in visual search the effects of conformality and display location on the allocation of visual attention. - Yeh, Michelle (Human Factors: The Journal of the Human Factors and Ergonomics Society)
Two experiments were performed to examine how frame of reference (world-referenced vs. screen-referenced) and target expectancy can modulate the effects of target cuing in directing attention for see-through helmet-mounted displays (HMDs). In the first experiment, the degree of world referencing was varied by the spatial accuracy of the cue; in the second, the degree of world referencing was varied more radically between a world-referenced HMD and a hand-held display. Participants were asked to detect, identify, and give azimuth information for targets hidden in terrain presented in the far domain (i.e., the world) while performing a monitoring task in the near domain (i.e., the display). The results of both experiments revealed a cost-benefit trade-off for cuing such that the presence of cuing aided the target detection task for expected targets but drew attention away from the presence of unexpected targets in the environment. Analyses support the observation that this effect can be mediated by the display : the world referenced display reduced the cost of cognitive tunneling relative to the screen referenced display in Experiment 1 ; this cost was further reduced in Experiment 2 when participants were using a hand-held display. Potential applications of this research include important design guidelines and specifications for automated target recognition systems as well as any terrain-and-targeting display system in which superimposed symbology is included, specifically in assessing the costs and benefits of attentional cuing and the means by which this information is displayed.